MAPPING HYPERTENSION DISEASE IN WOMEN AGED 25-45 YEARS AT TLOGOSARI KULON PRIMARY HEALTH CARE IN 2019 AND 2020 - Trianaldha Avina Farma; Suharyo Suharyo (Dian Nuswantoro Semarang, 2022)
Based on SIRANDU Semarang City, Tlogosari Kulon Primary Health Care (PHC) in 2019 had hypertension in the fifth position which reached 1.835 cases, and in 2020 it took third place that reached 3.091 cases. This study aims to find out the spread of hypertensive disease in women aged 25-45 years at Tlogosari Kulon PHC in 2019 and 2020. This study was a descriptive study that used an observation method with the entire population was hypertension case report in Tlogosari Kulon PHC in 2019 and 2020. The data source was from Morbidity Monthly Report (LB 1). The data was processed into new information using QGIS software. The results stated that in 2019 based on the village there were 100 cases, and in 2020 there were 221 cases. Meanwhile, compared to the number of female residents in 2019 the ratio was 0.22% or 100 out of 46.202 female residents. While in 2020 it reached 0.48% or 221 out of 46.202. In the results known that Muktiharjo Kidul Village was the area with the most amount of hypertension cases based on the village and the number of female residents. In presenting and reporting disease, it is better to use a geographic information system to find out a large number of people with hypertension. It can make it easier for PHC to prioritized the area and promoting health to maintain a healthy lifestyle so that people can avoid all risks of hypertension. It’s necessary to further research about the effect of the population on the incidence of hypertension. Keywords: Mapping, Hypertension, Women Aged 25-45 years Literature : 21 (2009-2020)